Identity of psychology: First results of systematic review - Esteves, Tiago (2017)
The thinking about the Psychology Identity is the background of this study, that helps to the answer of this question: Which is the exclusive aim of the psychologic intervention, that changes into singular when compared with any other profession or intervention? This statement, first research process stage more plural, disclose the process and the first products of a qualitative systematic literature review, grounded, explaining and describing all stages of the data collection and the synthesis. It is expose the first results obtained after the review of 202 studies, based on the qualification categories: published date, document typology, editor nationality, methodologic perspective, research method, sample size, publication impact factor and the citations quantity in the primary study.